Biopsychosocial view to pseudocyesis: A narrative review - Marzieh Azizi; Forouzan Elyasi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Pseudocyesis is a psychopathological clinical syndrome in which a non-pregnant woman firmly believes herself to be pregnant and manifests many symptoms and signs of pregnancy. Although the exact etiology of pseudocyesis has not been determined. Objective: This study was conducted with the aim of assessing the biopsychosocial view to pseudocyesis. Materials and Methods: A comprehensive search in electronic databases such as Google Scholar, PubMed, ScienceDirect, Web of Science, and Scopus was conducted between 1943-2016 to retrieve pseudocyesis related articles. For this purpose, 1149 articles were collected and 66 items were used. Results: Findings were classified into 2 main categories: a) pseudocyesis etiology, which could include (biological psychological factors and psychiatric disorders, and social factors); and b) pseudocyesis management. Conclusion: Pseudocyesis results from a multidimensional group of factors, and a holistic and comprehensive approach should be taken to its treatment. Cooperation between gynecologists and psychiatrists would likely be useful in addressing the condition.